Utility over novelty: How performance expectancy converts hedonic motivation, future expectations, and price sensitivity into private e-scooter purchase intention - İbrahim Kırçova; Munise Hayrun Sağlam; Ebru Enginkaya; Akın Konuk (PLoS ONE, 2026)
This study explains private e-scooter purchase intention through a mechanism-based process model that links value cues to performance beliefs and, subsequently, to motivational readiness to commit. We argue that hedonic motivation, forward-looking expectations about the technology, and lower price sensitivity strengthen perceived performance (usefulness, reliability, and access). In turn, perceived performance primarily increases purchase intention by enhancing perceived autonomy and competence, while consumer innovativeness plays a limited role in translating beliefs into purchase intention. We employ a sequential explanatory mixed-methods design. Survey data (n = 338) are analyzed using partial least squares structural equation modeling, followed by 26 semi-structured interviews to interpret the pathways and identify boundary conditions. The findings show that perceived performance is the key appraisal in the model. It is shaped by enjoyment, future expectations, and price evaluation, and it influences purchase intention mainly through autonomy and competence rather than novelty-oriented exploration. The qualitative findings show that infrastructure, safety, parking clarity, service continuity, and transparency in ownership cost shape the strength of this mechanism . Overall, the findings support a utility-first adoption logic. For managers addressing younger urban consumers in emerging-market contexts, the priority is to make performance credibility and ownership support visible through reliable product performance and robust after-sales assurance. For policymakers in similar settings, protected links and more transparent governance can stabilize perceived performance and strengthen confidence in everyday use..